IMPLEMENTATION OF E-SAMSAT SERVICES, MOBILE SAMSAT, AND DRIVE-THRU SAMSAT SERVICES OF MOTOR VEHICLE TAX RECEIPTS AT UPTD PPD CIKANDE IN 2019-2023 - Sari, Indah; Lestari, Dini Martinda; Afriani, Raden Irna (Yayasan Education and Social Center, 2025)
Motor vehicle tax is very important for development; motor vehicle tax contributes greatly to regional revenue. Tax is one of the sources of state revenue used to finance general expenses in government administration. The success of a country can be determined by the resources obtained through taxes. This study aims to test and analyze the effect of the Implementation of E-Samsat, Mobile Samsat, and Drive Thru Services on Motor Vehicle Tax (PKB) Revenue in Serang Regency. The research method used in this study is quantitative. The population is 86,620 motor vehicle taxpayers (WPKB) registered at the Samsat UPTD PPD Cikande Office, with this study involving 100 samples. The sampling technique uses the Slovin formula and a margin of error of 10%. The data collection technique is a survey method using a questionnaire with a Likert scale. The data analysis technique uses descriptive statistical analysis, data analysis tests, classical assumption tests, multiple regression analysis, and hypothesis testing using the SPSS version 25 test tool. The results of this study indicate that: The e-Samsat service in this study is 0.523 > 0.05, then H0 is accepted, and Ha is rejected. Mobile Samsat in this study is 0.000 < 0.05, then H0 is rejected, and Ha is accepted. The purpose of this study is to investigate and evaluate the impact that the implementation of E-Samsat, Mobile Samsat, and Drive Thru Services has had on the revenue generated by the Motor Vehicle Tax (PKB) in the Serang Regency market. A quantitative research approach was utilized for this study. This study included one hundred samples, and the population consists of 86,620 motor vehicle taxpayers (WPKB) registered at the Samsat UPTD PPD Cikande Office